From Paul to Valentinus: Christians at Rome in the first two centuries - Lampe, Peter (Continuum, 2003)
Investigating the rise and shape of the earliest churches in Rome, Lampe integrates history, archaeology, theology, and social analysis. He also takes a close look at inscriptional evidence to complement the reading of the great literary texts: from Paul's letter to the Romans to the writings of Clement of Rome, ≤Montanus and Valentinus.≤. 'I want to learn about the daily lives of the urban Roman Christians of the first two centuries, the realities of their social lives ... my ultimate goal is to contribute at least one element to a multidimensional interpretation of texts and faith ex